The effect of gluten-free diet among celiac patients aged 3-12 years old on BMI during 2006 to 2014 at Nemazee Teaching hospital - Mohsen Dehghani, Seyed (2018)
Introduction: Celiac disease (CD) is increasingly diagnosed and weight changes are common after adoption of a glutenfree diet (GFD) and there is concern that patients might gain further weight on a GFD. Objectives: This study examined toevaluate the impact of a GFD on the body mass index (BMI), whether favorable or unfavorable. Materials and methods: In this retrospective study, we reviewed electronic records of 44 patients with serologic study and intestinal biopsy confirmed CD who was visited in Nemazee hospital, Shiraz. All patients were put on GFD for 2 years and followed closely by pediatric gastroenterologist. BMIs were categories to four group underweight, normal weight, overweight and obese. Initial BMI and follow-up BMI was comparing together and also compared with general population. Result: At diagnosis, 27.27% of subjects were underweight, 63.64% normal and 9.09% were obese. On a GFD, 66.66% of underweight patients gained weight and became normal weight and 25% of normal weight and 75% of obese patients had increase weight; and the rest of the patients, BMI remained stable. The follow-up BMIs were statistically higher than initial BMIs (mean 17.17 vs. 15.62, p <0.0001). Conclusion: Individuals with celiac disease have lower BMI than the regional population at diagnosis. On the GFD, BMI is increased significantly in all categories.